Assessment of concomitant versus sequential trastuzumab on radiation-induced cardiovascular toxicity. (November 2017) - Yavas, G; Gultekin, M; Yildiz, O; Seyrek, M; Demirkol, S; Toy, H; Sargon, MF; Ozkayar, O; Uner, A; Yildiz, F; Akyol, F
There are limited data regarding effect of trastuzumab on radiation-induced cardiovascular toxicity when used sequentially or concomitantly. This experimental study aims to investigate effect of trastuzumab on radiation-induced cardiovascular toxicity with respect to the treatment sequence. One hundred and eight female Wistar albino rats were divided into six groups (G): G1 was control, G2 was trastuzumab, and G3 was radiotherapy (RT); G4 and G6 were sequential RT and trastuzumab; and G5 was concomitant RT and trastuzumab groups, respectively. Rats were killed at 6th h, 21st and 70th days after RT; thoracic aorta and heart samples were obtained. Transthoracic echocardiography and functional studies evaluating relaxation of thoracic aorta were performed. Subendothelial edema scores of thoracic aorta samples at 21st and 70th days were higher in RT groups (G3, G4, G5, and G6) ( p < 0.001). There was a deterioration of relaxation responses of thoracic aorta samples in RT groups ( p < 0.001). Cardiac fibrosis (CF) scores revealed detrimental effect of RT beginning from 6th h and trastuzumab from 21st day. RT groups showed further deterioration of CF at 70th day. Ejection fraction, left ventricular mass, and fractional shortening were significantly decreased in G4, G5, and G6. Trastuzumab may increase pathological damage in cardiovascular structures when used with RT regardless of timing.